Chronic lymphoproliferative diseases and cardiovascular risk (a literature review) - Samura, B. B.; Panasenko, M. O. (Zaporozhye Medical Journal, 2022)
Heart dysfunction that occurred after using of anticancer drugs and monoclonal antibodies may be a limit factor in treatment of chronic lymphoproliferative diseases (CLPD). Cancer therapy-related cardiovascular toxicity include hypotension, hypertension, arrhythmias, conduction disturbances, pericarditis, thromboembolic events, heart failure, death. The risk of cardiotoxicity may be increased by some factors that include drug exposure, age, history of heart diseases, arterial hypertension, drug combination, previous radiotherapy or chemotherapy. The aim of the work is to assess the impact of anticancer treatment on the occurrence of cardiovascular events in patients with CLPD according to the world scientific literature data. It is important to detect the cardiovascular toxicity before the development of clinical manifestations of damage to the myocardium and blood vessels. The role of markers in identifying the risk group of adverse cardiovascular events remains unclear. Early diagnostics and determination of prognostic factors of cardiovascular toxicity, which develop after anticancer therapy of CLPD, are important and not solved problems. Conclusions. The prognosis for the development of cardiovascular events after antitumor treatment of CLPD remains unfavorable. Clinical monitoring, imaging methods, determination of the biomarker levels (natriuretic peptides, troponins) for cardiotoxicity risk stratification are recommended during antitumor treatment to identify early signs and risk of cardiotoxicity. The use of the latest biomarkers and their combinations may be a way to improve the assessment of the cardiotoxicity risk in CLPD. To date, there is no sufficient evidence on the feasibility of routine determining these biomarkers, which indicates the need to plan new studies.